The History of Geopark Development in Australia, A New Way Forward - Angus Robinson (Geoconservation Research, 2022)
Geoparks in Australia have had a complex recent history. Following the demise of the former Kanawinka UNESCO Geopark in 2012, two potential UNESCO Global Geopark projects supported by local government agencies and embracing large areas were initiated in other Australian regions in 2016. These were for the Etheridge Geopark in Far North Queensland and the Warrumbungle Geopark in New South Wales, both featuring important volcanic phenomena. However, both proposals failed to proceed to the stage where they could be nominated by any Australian government as Aspiring UNESCO Global Geoparks. This paper focuses on the genesis of these issues and what steps have been undertaken, lessons learnt, and measures that are now being undertaken to obtain government support and broad community engagement for geopark projects. In essence, it has now been recommended that the proposal should avoid reference to the word ‘geopark’ and focus instead on communicating the concept of a ‘GeoRegion.’